2019
DOI: 10.1186/s12885-019-5863-2
|View full text |Cite
|
Sign up to set email alerts
|

Long term outcome after 48 Gy stereotactic ablative body radiotherapy for peripheral stage I non-small cell lung cancer

Abstract: Background To evaluate the outcome of patients treated with stereotactic ablative body radiotherapy (SABR) with curative intent for stage I non-small cell lung cancer (NSCLC) with regard to local, regional and distant tumor control, disease-free survival (DFS), overall survival (OS) and toxicity. Methods Data of 300 patients treated with SABR for NSCLC cancer for the period of November 2007 to June 2016 were retrospectively analyzed. Of which, 189 patients had single pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…In the past decade, important advances have been achieved in the multimodal treatment of inoperable stage III NSCLC. The introduction of VMAT has decreased the toxicity of TRT [ 20 22 ] and routine concurrent chemo-radiotherapy has constantly been improved [ 23 ]. The PACIFIC trial has changed the landscape of thoracic oncology with unprecedented improvements in OS and PFS [ 7 , 8 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the past decade, important advances have been achieved in the multimodal treatment of inoperable stage III NSCLC. The introduction of VMAT has decreased the toxicity of TRT [ 20 22 ] and routine concurrent chemo-radiotherapy has constantly been improved [ 23 ]. The PACIFIC trial has changed the landscape of thoracic oncology with unprecedented improvements in OS and PFS [ 7 , 8 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…A number of prospective, multicenter clinical trials have demonstrated excellent local control of early-stage NSCLC with minimal levels of acute and late toxicity using a variety of fractionation options including 54–60 Gy in three fractions, 48 Gy in four fractions, and 30–34 Gy in one fractions for tumors which are located peripherally (outside of 2 cm from the proximal bronchial tree) ( 24 27 ) SABR is also feasible to deliver to tumors which are located within 2 cm of the proximal bronchial tree (central or ultracentral tumors), through the use of more cautious dose fractionation options including 60 Gy in eight fractions and 50 Gy in five fractions ( 28 , 29 ).…”
Section: Standard Of Care Treatment: Sabrmentioning
confidence: 99%
“…Dose-volume limits need to be identified to predict complications involving central structures such as the proximal airways, heart, esophagus, and great vessels, especially in older patients (24). SABR provides a long-term local control and survival for peripheral stage I NSCLC with a low toxicity (25).…”
Section: Early Lung Cancermentioning
confidence: 99%